Optimizing storage emissions of wood flakes by gas sensor controlled thermal oxidation of lipids. (October 2018) - Paczkowski, Sebastian; Jaeger, Dirk; Pelz, Stefan
Abstract: Emissions in pellet storages caused by the autooxidation of lipids have a negative impact on human health and lead to unpleasant odors. This study investigates (1) the emissions of softwood flakes during temperature treatments (150°C-240 °C), (2) the online monitoring of these emissions with gas sensors, (3) the impact of the thermal treatments on the lipid content in the flakes and (4) the correlation between the lipid content and the storage emissions. The results show a correlation between the temperature during the treatment, the α-pinene, furfural, and 2-methoxyphenol emissions, and the gas sensor response. The decrease of the lipid content is correlated to a decrease in storage emissions, especially hexanal and carbon monoxide. It is discussed if higher drying temperatures during pellet production can reduce the storage emissions of the pellets. The increasing fire risk in the dryer could be controlled by the gas sensors. Graphical abstract: Image 1 Highlights: Drying of wood flakes at high temperatures leads to a temperature dependent volatile emission profile. This profile can be monitored by gas sensors in order to reduce the fire risk of high temperature drying. High temperatures reduce the lipid content of the wood flakes. A reduced lipid content leads to lower emissions during wood flake storage.